The Effect of Total Physical Response Technique on the Eleventh Graders' Speaking Ability at SMA PSKD 7 Depok - Suryaningrum, Dwi (JET (Journal of English Teaching), 2017)
AbstractThe objective of this research was to investigate whether or not there was an effect of using Total Physical Response (TPR) technique in students’ speaking ability to the eleventh graders at SMA PSKD 7 Depok. To attain the aim, both pre and the post-test were administered to two classes consisting 25 students each. Data analysis showed that there is a significant effect of using TPR technique in students’ speaking ability; it can be seen from the mean score of the post test between experimental (67.36) and control (51.52) class. Based on the findings, it could be concluded that the use of TPR technique was effective to improve Eleventh graders’ speaking ability. Keywords: experimental research, total physical Response technique, speaking ability